2022
DOI: 10.1038/s42003-022-03202-5
|View full text |Cite
|
Sign up to set email alerts
|

A global microbiome survey of vineyard soils highlights the microbial dimension of viticultural terroirs

Abstract: The microbial biodiversity found in different vitivinicultural regions is an important determinant of wine terroir. It should be studied and preserved, although it may, in the future, be subjected to manipulation by precision agriculture and oenology. Here, we conducted a global survey of vineyards’ soil microbial communities. We analysed soil samples from 200 vineyards on four continents to establish the basis for the development of a vineyard soil microbiome’s map, representing microbial biogeographical patt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 71 publications
4
43
1
1
Order By: Relevance
“…Despite the use of different primers for 16S rRNA gene amplicon sequencing between the studies, the bacterial communities found in our samples were similar to previous findings, with a predominant relative richness of Actinobacteria , Proteobacteria , Bacteroidota , Firmicutes , Acidobacteria , Chloroflexi , Myxococcota , and Gemmatimonadota ( Samad et al, 2017 ; Berlanas et al, 2019 ; Liang et al, 2019 ; Deyett and Rolshausen, 2020 ; Dries et al, 2021a ; Swift et al, 2021 ). Most of these phyla represent the core microbiome of vineyard topsoils identified through a global microbiome survey within 200 vineyards collected in 13 countries ( Gobbi et al, 2022 ). Samad et al (2017) found that lower diversity was recovered by cultivation from rhizosphere samples compared with community sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of different primers for 16S rRNA gene amplicon sequencing between the studies, the bacterial communities found in our samples were similar to previous findings, with a predominant relative richness of Actinobacteria , Proteobacteria , Bacteroidota , Firmicutes , Acidobacteria , Chloroflexi , Myxococcota , and Gemmatimonadota ( Samad et al, 2017 ; Berlanas et al, 2019 ; Liang et al, 2019 ; Deyett and Rolshausen, 2020 ; Dries et al, 2021a ; Swift et al, 2021 ). Most of these phyla represent the core microbiome of vineyard topsoils identified through a global microbiome survey within 200 vineyards collected in 13 countries ( Gobbi et al, 2022 ). Samad et al (2017) found that lower diversity was recovered by cultivation from rhizosphere samples compared with community sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…One requirement of the modern research in plant‐associated microbiomes is to extend investigations from a confined range, e.g . microcosms or single fields (Vink et al ., 2021b), to wide ecosystem scales to unravel the selective forces that influence the microbiome associated with plant across the heterogeneous conditions of real‐word ecosystems (Delgado‐Baquerizo, 2022; Gobbi et al ., 2022). Ecosystem‐scale studies can offer important contributions that can set the basis of future framework for targeted agriculture (Trivedi et al ., 2021) and microbial synthetic communities applications (Delgado‐Baquerizo, 2022) to support productivity and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have explored the effects of biogeography, genotype and vintage on the composition of the prefermentation must (Bokulich et al, 2014; Kamilari et al, 2021; Li et al, 2022; Morrison‐Whittle & Goddard, 2018) and soil microbiome (Gobbi et al, 2022; Mezzasalma et al, 2018; Zarraonaindia et al, 2015), while the epiphytic grapevine microbiome (surface of leaves and berries) has attracted less attention (Portillo et al, 2016). In a pioneering study, Bokulich et al (2014) showed that biogeography was the stronger factor affecting must microbiome, while cultivar and vintage were less important confounding factors affecting microbial composition.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the grapevine tissue explored, most studies have tried to disentangle the effects of one (e.g., biogeography for a single cultivar or cultivar in different regions) (Liu et al, 2020; Zhang et al, 2020) or two of these factors (e.g., biogeography and cultivar) (Mezzasalma et al, 2018; Vitulo et al, 2019), while the combinatory effects of all three factors in the formation of the grapevine microbiome has not been explored in depth. The effect of biogeography has been studied at different scales: vineyard scale (Bokulich et al, 2016), viticultural zone scale (Knapp et al, 2021), national scale (Liu et al, 2020; Vitulo et al, 2019) and recently global scale for vineyard soils (Gobbi et al, 2022). All these studies agree that the degree of similarity of microbial community composition decays with increasing geographic distance and this implies that microbial community assemblages are influenced by spatial factors.…”
Section: Introductionmentioning
confidence: 99%